Pharmacognostical and Phytochemical Evaluation of Kigelia Pinnata (Jacq) dc. (Bignoniaceae) - Root (International Journal of Ayurveda and Pharma Research, 2023)
Kigelia pinnata (Jacq) DC. (Family Bignoniaceae) commonly known as “Sausage tree” is reputed African folklore drug and abundantly found throughout India. Its root is used traditionally in cancer, diabetes, gastrointestinal problems, constipation, gynecological complaints etc. The present paper highlights the pharmacognostical and phytochemical studies along with HPTLC fingerprint profile of K.pinnata root for its botanical identification and standardization. Pharmacognostical analysis of K. pinnata root comprises of organoleptic characters, transverse section of root along with powder microscopy. It was analyzed through relevant physicochemical parameters and qualitative tests for various functional groups. HPTLC was carried out after organizing appropriate solvent system. TS and powder microscopy reveals presence of large amount of fibres, parenchymas and vessels filled with tannin content. Preliminary qualitative analysis proves the presence of flavanoids, tannins, saponins, steroids and phenolic compounds. The preliminary physico-chemical analysis shows water-soluble extract 22.78% w/w, alcohol-soluble extract 21.10% w/w and loss on drying at 105°C was 10.40% w/w with 5.2 pH. HPTLC were carried out in which maximum 4 & 5 peaks at 254nm & 366nm respectively. The anatomical characters and values obtained from analytical study can help in standardization.